Meeting on the decline of the urban House Sparrow "Passer domesticus": Newcastle 2009 (24-25 Feb) - Laet, Jenny De; Summers-Smith, Denis J.; Mallord, John (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The symposium on the status of the House Sparrow "Passer domesticus", in the urban environment held during the 24th IOC aroused considerable interest. Following this it was agreed to set up a "working group" to foster exchange of ideas among researchers concerned with this problem that is of considerable biological significance. After the first meeting held in London 2007 (ISSP 31: 27-37), a second meeting was held in Newcastle. On the first day several talks were presented concerning the decline of the urban House Sparrow, the associated habitat and different monitoring techniques.
Keywords: wróblowe; ornitologia; czasopismo